Influence of curing temperature on cement paste microstructure measured by 1H NMR relaxometry. (August 2019) - Gajewicz-Jaromin, Agata M.; McDonald, Peter J.; Muller, Arnaud C.A.; Scrivener, Karen L.
Abstract: 1 H nuclear magnetic resonance (NMR) relaxometry, supported by X-Ray diffraction and thermogravimetric analysis, has been used to characterise microstructure of white cement pastes underwater cured at temperatures in the range 10 °C to 60 °C. As the temperature increases, so the C-S-H, capillary pore water and interhydrate pore water content all increase; the ettringite and gel pore water content decrease; and the Portlandite content stays constant. A non-linear increase in the C-S-H 'solid' and 'bulk' densities, that exclude and include gel pore water respectively, has been observed with the increase of temperature. This is accompanied by a decrease in C-S-H water content but no change in the Ca/(Si + Al) ratio. The increase in the C-S-H 'solid' density has been attributed to a decrease in the number of locally stacked C-S-H layers. The increase in the C-S-H 'bulk' density is additionally attributed to the decrease in the gel porosity. Graphical abstract: Unlabelled Image